Involvement of CBF in the fine-tuning of litchi flowering time and cold and drought stresses - Shan, Xiaozhen; Yang, Yun; Wei, Shuoqi; Wang, Chao; Shen, Weishi; Chen, Hou-bin; Shen, Ji-yuan (Frontiers in Plant Science, 2023)
Litchi (Litchi chinensis) is an economically important fruit tree in southern China and is widely cultivated in subtropical regions. However, irregular flowering attributed to inadequate floral induction leads to a seriously fluctuating bearing. Litchi floral initiation is largely determined by cold temperatures, whereas the underlying molecular mechanisms have yet to be identified. In this study, we identified four CRT/DRE BINDING FACTORS (CBF) homologs in litchi, of which LcCBF1, LcCBF2 and LcCBF3 showed a decrease in response to the floral inductive cold. A similar expression pattern was observed for the MOTHER OF FT AND TFL1 homolog (LcMFT) in litchi. Furthermore, both LcCBF2 and LcCBF3 were found to bind to the promoter of LcMFT to activate its expression, as indicated by the analysis of yeast-one-hybrid (Y1H), electrophoretic mobility shift assays (EMSA), and dual luciferase complementation assays. Ectopic overexpression of LcCBF2 and LcCBF3 in Arabidopsis caused delayed flowering and increased freezing and drought tolerance, whereas overexpression of LcMFT in Arabidopsis had no significant effect on flowering time. Taken together, we identified LcCBF2 and LcCBF3 as upstream activators of LcMFT and proposed the contribution of the cold-responsive CBF to the ﬁne-tuning of ﬂowering time.